Tracing the Arc: The Shifting Conceptualizations of Educational "Disadvantage" and "Diversity" at the University of Wisconsin-Madison - Allweiss, Alexandra; Grant, Carl (My University, 2014)
This article calls attention to the shifting conceptualizations of belonging and inclusion at universities in the U.S. through shifting framings of ?educational disadvantage? and ?diversity?. Historically these concepts have been used in various and shifting ways to think about the ?Other? and to determine the lines of inclusion and exclusion to access to higher education spaces. This article uses a leading public university, the University of Wisconsin-Madison, as a histori-cal case study to examine the ways the university has responded to those who have historically been excluded from public higher education spaces and the ways inclusion has been expanded and redefined through struggle. This case study is an invitation to carefully consider the current discourses and policy debates about university ?diversity? efforts and the inclusion of ?disadvantaged? students. We raise questions about what inclusion means.